2020
DOI: 10.15761/ifnm.1000289
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of hypocalcemia in COVID-19

Abstract: Background: Preliminary data suggest that hypocalcemia is common among patients with coronavirus 2019 admitted to the hospital.Objective: To examine the prognostic value of hypocalcemia in the setting of COVID-19.Methods: Literature search (Pubmed) until September 15, 2020. Search terms include hypocalcemia, COVID-19, mortality, complications. Retrospective studies are reviewed due to lack of randomized trials.Results: Hypocalcemia is the most common electrolyte abnormality in patients with COVID-19 admitted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…However, the role of hypocalcemia in COVID-19 infection is not fully known yet. It can be speculated that the "consumption" of circulating Ca for the virus to enter the host cells, as noted by Mikail and Mali [52] , may contribute to hypocalcemia. Tezcan et al reported that low basal Ca levels are associated with higher mortality rates, higher intensive care unit and mechanical ventilation requirements, and more extended hospital stay [53] .…”
Section: Discussionmentioning
confidence: 98%
“…However, the role of hypocalcemia in COVID-19 infection is not fully known yet. It can be speculated that the "consumption" of circulating Ca for the virus to enter the host cells, as noted by Mikail and Mali [52] , may contribute to hypocalcemia. Tezcan et al reported that low basal Ca levels are associated with higher mortality rates, higher intensive care unit and mechanical ventilation requirements, and more extended hospital stay [53] .…”
Section: Discussionmentioning
confidence: 98%
“…In a review by Mikhail et al, (40), the frequency of hypocalcaemia among patients with COVID-19 was reported to be 9.5-78%. In the general population, common causes of hypocalcaemia include chronic kidney disease, vitamin D deficiency, hypomagnesaemia, drugs and hypoparathyroidism (41).…”
Section: Discussionmentioning
confidence: 99%
“…In the general population, common causes of hypocalcaemia include chronic kidney disease, vitamin D deficiency, hypomagnesaemia, drugs and hypoparathyroidism (41). So far, the exact cause (s) of hypocalcaemia in COVID-19 patients is/ are not known (40). However, some plausible hypotheses have been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…This "consumption" of Ca 2+ for the virus entry into cells might contribute to hypocalcemia and more pronounced inflammation, which further stimulates the activity of the coagulation cascade. Expectedly, multiple studies have shown significant association between hypocalcemia and inflammatory markers that reflect the severity of COVID-19 (37).…”
Section: Pathophysiology Of Hemostatic Disorders In Covid-19mentioning
confidence: 99%